2021
DOI: 10.32404/rean.v8i3.5997
|View full text |Cite
|
Sign up to set email alerts
|

Plantability and Influence of the Application of Graphite Associated With the Chemical Treatment of Soybean Seeds

Abstract: Brazil stands out among the world's largest soy producers. The uniformity in the deposition of seeds and the correct distribution of plants are important factors for the crop to express its maximum productive potential. The present study aimed to evaluate the influence of the lubricant agent “graphite”, applied during and after the chemical treatment of soybean seeds in function of its longitudinal distribution at different operating speeds. For this purpose, a seeder with mechanical type feeder was used, at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…It was observed that the increase in the operational speed of sowing up to the speed of 6 km h -1 did not impact the fault spacing index in the equidistant distribution, a result that diverges from the statement made by Pereira et al (2021) that the increase in speed, from 4 to 6 and 8 km h -1 , promoted a higher index of faulty spacing, potentially caused by the greater turbulence suffered by the seeds inside the conductor tube.…”
Section: Resultscontrasting
confidence: 61%
“…It was observed that the increase in the operational speed of sowing up to the speed of 6 km h -1 did not impact the fault spacing index in the equidistant distribution, a result that diverges from the statement made by Pereira et al (2021) that the increase in speed, from 4 to 6 and 8 km h -1 , promoted a higher index of faulty spacing, potentially caused by the greater turbulence suffered by the seeds inside the conductor tube.…”
Section: Resultscontrasting
confidence: 61%
“…The fluidity of the seeds in the feeder is affected by the operating speed. Chemical seed treatment can also interfere with sowing quality and affect seed slip in the feeder (Pereira et al 2021b).…”
Section: Resultsmentioning
confidence: 99%
“…This indicator can be also determined as a ratio of square deviation of the seed average weight falling on a measurement distance in individual rows to an average weight for the whole seed drill. In turn, an indicator of lateral unevenness of seed sowing is defined as a ratio of square average deviation in a row to average deviation in a row 38 . The indicator of lateral seed sowing unevenness is commonly defined for point seed drills 38 .…”
Section: Materials and Study Methodsmentioning
confidence: 99%
“…In turn, an indicator of lateral unevenness of seed sowing is defined as a ratio of square average deviation in a row to average deviation in a row 38 . The indicator of lateral seed sowing unevenness is commonly defined for point seed drills 38 .…”
Section: Materials and Study Methodsmentioning
confidence: 99%